Makna Budaya Cerpen Mama Eta Karya Silvester Petara Hurit (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to describe the cultural meaning of the short story Mama Eta by Silvester Petara Hurit. This study uses a descriptive qualitative method with a hermeneutic approach. The results of the study of cultural meaning in the short story Mama Eta by Silvester Petara Hurit can be concluded that there are cultural meanings, namely first, the cultural meaning of simplicity, second the cultural meaning of religiosity as an oasis of life, third the cultural meaning related to respect for ancestors, fourth the cultural meaning related to the role of women in social structures, and fifth the cultural meaning related to collectivity and social harmony.